2012
DOI: 10.1108/17581181211230685
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a multimedia Wiki‐based class text and a traditional textbook

Abstract: Purpose -The purpose of this paper is to provide an improved understanding of how a wiki text compares to the use of a traditional text, and to provide an improved understanding of how integrating audio and video into a learner-created wiki class text impacts learning. Design/methodology/approach -For this case study, a causal comparative research design was used to compare students' learning between the two groups. A one-way multivariate analysis of variance (MANOVA) was used to analyze the quantitative data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Given the increased use of e-books both in and out of the classroom (Blume, 2013;Hu, 2011;Rockinson-Szapkiw, 2011), it is important to examine whether paper and screens as a reading medium are equivalent with regard to efficiency and effectiveness when reading and studying. Although preliminary, our studies' findings indicate that the medium might not matter when students are engaged in simple, familiar, or low-stakes tasks involving reading, processing, and synthesizing information, especially under no time pressure.…”
Section: Implications For Formal and Informal Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increased use of e-books both in and out of the classroom (Blume, 2013;Hu, 2011;Rockinson-Szapkiw, 2011), it is important to examine whether paper and screens as a reading medium are equivalent with regard to efficiency and effectiveness when reading and studying. Although preliminary, our studies' findings indicate that the medium might not matter when students are engaged in simple, familiar, or low-stakes tasks involving reading, processing, and synthesizing information, especially under no time pressure.…”
Section: Implications For Formal and Informal Learningmentioning
confidence: 99%
“…Among youth, a 2012 survey of U.S. 12-to 17-yearolds reported that 93% have home computer access, 37% own a smartphone, and 23% have a tablet computer; one in four reported that they are "cell-mostly" Internet users, who use their phone to go online most of the time (Madden & Lenhart, 2013). Moreover, tablets and electronic books are being adopted by students of all ages for access to textbooks and other instructional materials (Hu, 2011;Rockinson-Szapkiw, 2011) and recently, the Los Angeles Unified District approved iPads for every child in the district's schools (Blume, 2013).…”
Section: Introductionmentioning
confidence: 99%